2010
DOI: 10.1186/2047-783x-15-11-483
|View full text |Cite
|
Sign up to set email alerts
|

Tissue reaction to sealing materials: different view at biocompatibility

Abstract: The biodegradability of root canal sealers in areas other than the root canal system is crucial to the overall success rate of endodontic treatment. The aim of the present study was to investigate, the cell and tissue reaction to GuttaFlow and AHPlus, both in vitro and in vivo. For the in vitro experiments the materials were incubated with Human Periodontal Ligament Fibroblasts and cell proliferation and cytotoxicity analyses were performed. Additional fluorescence-microscope stainings were carried out in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 24 publications
4
27
0
Order By: Relevance
“…Furthermore, all the groups demonstrated intense granulation reaction with the presence of a larger number of blood vessels, which clinically suggested the presence of hyperemic areas (P=0.002). The granulation reaction induced by the cements was predictable in the initial period, since it functioned as a pathway for the macrophages to reach the implant site (Ghanaati et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, all the groups demonstrated intense granulation reaction with the presence of a larger number of blood vessels, which clinically suggested the presence of hyperemic areas (P=0.002). The granulation reaction induced by the cements was predictable in the initial period, since it functioned as a pathway for the macrophages to reach the implant site (Ghanaati et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…After the period of 7 days, the RMO ® and Transbond ® demonstrated intense inflammatory infiltrate when compared with the control group (P=0.004). This initial inflammatory response reflected the attempt by the tissue to induce the process of degradation of the materials through the inflammatory cells recruited to the surrounding tissue and in the direction towards the surface of the cements (Ghanaati et al 2010, Malkoc et al 2010. In addition, it suggested that the elution of toxic substances released by these cements was capable of stimulating the production of reactive oxygen species (ROS), and increasing the expression of COX-2/PGE 2, which are potent chemical mediators, capable of potentiating the inflammatory response (Costa et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of root canal filling is to promote the hermetic sealing of root canals, neutralize the remaining microbiota and stimulate mineralization of the pulp stump without causing toxic effects on the cells of the periapical region (1). Therefore, the biological properties of root canal sealers and the degree of cytotoxicity or stimulation they may have on different cells, including fibroblasts, osteoblasts and cementoblasts must be evaluated (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have evaluated the biological effects of sealers based on zinc-oxide-eugenol (ZOE), glass ionomer, epoxy resin, silicones, calcium silicate, methacrylate resin and sealers containing calcium hydroxide in their composition (1). The in vitro cytotoxicity of different types of sealers has been evaluated by direct exposure of different cell lines to sealers or their components solubilized in liquid media (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Healing after treatment depends directly on the characteristics of the material used for canal sealing. According to the literature, the materials should not cause irritation of the periapical tissue, because this may result in failure of endodontic treatment (1).…”
Section: Introductionmentioning
confidence: 99%